2019
DOI: 10.1016/j.jort.2019.100225
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing teenagers’ recreational forest use in a densely-populated region in Switzerland

Abstract: Factors influencing teenagers' recreational forest use in a densely-populated region in Switzerland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Then, the frequency of the forest visits for a walk gradually decreased after 49 years old. The results indicated the importance of introducing the habit of visiting the forest starting at a younger age [32][33][34][35]. Oppliger et al [34] found that 42% of the respondents were forbidden by their parents to visit forests in their childhood.…”
Section: Frequency Of the Forest Visits According To The Driversmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the frequency of the forest visits for a walk gradually decreased after 49 years old. The results indicated the importance of introducing the habit of visiting the forest starting at a younger age [32][33][34][35]. Oppliger et al [34] found that 42% of the respondents were forbidden by their parents to visit forests in their childhood.…”
Section: Frequency Of the Forest Visits According To The Driversmentioning
confidence: 99%
“…The results indicated the importance of introducing the habit of visiting the forest starting at a younger age [32][33][34][35]. Oppliger et al [34] found that 42% of the respondents were forbidden by their parents to visit forests in their childhood. Moreover, the children who joined a youth group interested in the forest (scouts) had a higher frequency of forest visits in their teenage years.…”
Section: Frequency Of the Forest Visits According To The Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of great significance to study how to improve the satisfaction of tourists and then improve the willingness of tourists to visit urban forest parks to promote the development of forest tourism. Tourists' willingness to visit urban forest parks is affected by many factors, such as the frequent use of electronic media [15], frequent forest visits during childhood [15], and seasonal factors [16]. Some scholars have mentioned the impact of forestry infrastructure [17,18] on the development of forest tourism [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%